An Evaluation Strategy for the Moodle Learning Environment based on Blooms Taxonomy. - Bagarukayo, Emily; Weide, Theo P. van der; Lubega, Jude (In CSEDU, 2011)
Learning environments are based on core foundations, describing how knowledge is acquired and used, the underlying pedagogical philosophy, the supported learning process, the role of technique and culture, and related pragmatics. Bloom's Digital Taxonomy (BDT) describes the various thinking skills, ranging from low to high order thinking skills. We relate the learning environment Moodle to BDT by relating the core foundations with the thinking skills. We evaluate Moodle from different points of views: - methods, effectiveness and comparison with the existing learning environments.``
Keywords: Learning Environment; Blooms Digital Taxonomy; Moodle; Higher Order Cognitive Skills